Advantages and Pitfalls of Fructosamine and Glycated Albumin in the Diagnosis and Treatment of Diabetes - Danese, Elisa (J Diabetes Sci Technol, 2015)
The efficient diagnosis and accurate monitoring of diabetic patients are cornerstones for reducing the risk of diabetic complications. The current diagnostic and prognostic strategies in diabetes are mainly based on two tests, plasma (or capillary) glucose and glycated hemoglobin (HbA1c). Nevertheless, these measures are not foolproof, and their clinical usefulness is biased by a number of clinical and analytical factors. The introduction of other indices of glucose homeostasis in clinical practice such as fructosamine and glycated albumin (GA) may be regarded as an attractive alternative, especially in patients in whom the measurement of HbA1c may be biased or even unreliable. These include patients with rapid changes of glucose homeostasis and larger glycemic excursions, and patients with red blood cell disorders and renal disease. According to available evidence, the overall diagnostic efficiency of GA seems superior to that of fructosamine throughout a broad range of clinical settings. The current method for measuring GA is also better standardized and less vulnerable to preanalytical variables than those used for assessing fructosamine. Additional advantages of GA over HbA1c are represented by lower reagent cost and being able to automate the GA analysis on many conventional laboratory instruments. Although further studies are needed to definitely establish that GA can complement or even replace conventional measures of glycemic control such as HbA1c, GA may help the clinical management of patients with diabetes in whom HbA1c values might be unreliable.